2002
DOI: 10.1063/1.1524303
|View full text |Cite
|
Sign up to set email alerts
|

Study of the relaxation process during InGaAs/GaAs (001) growth from in situ real-time stress measurements

Abstract: Strain evolution during In0.2Ga0.8As/GaAs (001) growth by molecular beam epitaxy has been monitored in real time. We have detected that three main relaxation stages, related to different mechanisms, take place during growth, and we have obtained the thickness range where those mechanisms are active. The in situ measured relaxation behavior in the plastic stages has been described by means of a simple equilibrium model that takes into account dislocations generation and interaction between them. The excellent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In all cases, we observe a linear increase in ⌺ , indicating pseudomorphic growth along ͓110͔. 8 This behavior is in complete agreement with QWR formation, which as a result of their geometry relax stress only in the direction perpendicular to their orientation and, so far, no stress relaxation due to QWR formation can be measured in ͓110͔ direction. 9,12 Accordingly, ⌺ evolution in ͓110͔ corresponds unequivocally to the total amount of InAs grown.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In all cases, we observe a linear increase in ⌺ , indicating pseudomorphic growth along ͓110͔. 8 This behavior is in complete agreement with QWR formation, which as a result of their geometry relax stress only in the direction perpendicular to their orientation and, so far, no stress relaxation due to QWR formation can be measured in ͓110͔ direction. 9,12 Accordingly, ⌺ evolution in ͓110͔ corresponds unequivocally to the total amount of InAs grown.…”
supporting
confidence: 69%
“…Stress evolution during this process has been obtained by optical monitorization of the substrate curvature. [8][9][10] This technique provides a direct, in situ, and in real time measurement of the film accumulated stress, ⌺ ͑stress integrated along the layer thickness͒. 8,10 We use thinned InP͑001͒ substrates ͑190 m͒ to improve sensitivity, elongated along ͓110͔ to detect stress variations in this direction.…”
mentioning
confidence: 99%
“…Unfortunately, only heterostructures of one particular composition (In 0.52 Al 0.48 As/In 0.53 Ga 0.47 As) can be grown lattice-matched to a commercial binary substrate (InP). In order to maximize the flexibility in the choice of alloy composition, and correspondingly to tune the g factor, several research studies have been carried out to understand the mechanisms of strain relaxation in these systems in cases where a lattice mismatch to the substrate exists [6][7][8]. It was demonstrated that a defectfree region with an arbitrary In concentration can be obtained both on GaAs and InP substrates by inserting a step-graded buffer layer (BL) with increasing In composition in order to smoothly adapt the lattice constant of the substrate to the one of the topmost layer.…”
Section: Introductionmentioning
confidence: 99%
“…To understand and control the growth of InAs on GaAs(001), therefore, in situ observation of internal strain of the nanoislands is essential. So far, strain evolution during layer-by-layer growth of InGaAs/GaAs has been measured by detecting the bending of the substrate that is shaped as a cantilever [20]. In this method, the average strain of the InGaAs layer was estimated from the accumulated stress that was given to the substrate.…”
Section: Discussionmentioning
confidence: 99%